Berberine Contents as a Quality Marker in Medicinal Plants and Amounts of Berberine Passing into Serum - Cansu Aydın, Sabire; Kalaycıoğlu, Zeynep; Erim, F. Bedia (Bentham Science Publishers Ltd., 2024)
Background: Berberine is an alkaloid found in some medicinal plants. Berberine-containing plants have traditionally been used in the treatment of diseases since ancient times. Berberine is a natural compound that has an important place in traditional Chinese medicine. Currently, berberine is being evaluated extensively in clinical trials and is one of the natural products on which most scientific research studies have been published. Numerous clinical and pharmacological research results have been published on the therapeutic effect of berberine against cancer, diabetes, and heart disease Objective: The first purpose of this review is to display the berberine content of plants found in different regions of the world, and the second purpose is to provide the amount of berberine passing into the serum. Methods: Herbal supplements and extracts prepared from plants containing berberine are commercially marketed. The content of berberine in plants varies widely, and berberine is a quality indicator for many medicinal plants. Results: Different analytical methods have been developed for reliable berberine analysis. Plant and serum berberine levels reported between the years 2013 and 2022 in journals covered by SCI are collected in this review article. Conclusion: We hope that this overview of berberine amounts will be useful in future pharmaceutical and pharmacokinetic studies.